Machine learning advances volatile fatty acids production in anaerobic sludge fermentation: linking substrate traits to operation parameters - Yuhang Zhou; Zhen Lu; Libing Chen; Zihan Ma; Zhouhao Shi; Dongshan Yang; He Liu (Journal of Cleaner Production, 2026)

Effect of electron beam irradiation on microstructure and performance of polyamide/polysulfone composite membranes for water treatment - Hejie Shen; Zheng’ao Zhang; Fengyao Wang; Zhe Chen; Lei Yao; Junjie Liu; Libing Qian; Zhiyuan Chen; Atsushi Yabuuchi; Atsushi Kinomura; Yoshinori Kobayashi; Hamdy F.M. Mohamed (Journal of Environmental Chemical Engineering, 2026)

Electrosynthesis of hydrogen peroxide via two-electron water oxidation reaction: Mechanistic insights, materials design, and practical feasibility - Yuanzhi Lei; Libing Gao; Chen Ling; Shao Qing Guo (Chemical Engineering Journal, 2026)

Research on sample preparation of calcareous and silica sand with air pluviation method - Ruiming Liu; Libing Li; Naman Maimaiti; Peng Chen (Marine Georesources & Geotechnology, 2026)

Reliability analysis of CRTS III slab ballastless track structure on bridge based on probability density evolution - Li Song; Libing Chen; Maodong Zhu; Wenchang Zhang; Jian Hou (Engineering Structures, 2026)

Prediction of water quality in the middle area of Yangtze River using efficient machine learning model - Jingjing Xia; Wenya Chen; Libing Liu; Ziyan Li; Yutong Wang; Chaohao Yang; Jin Zeng (Environmental Geochemistry and Health, 2025)

One-step dual-functional modification of Ni-rich cathodes via DFT prediction for high-rate quasi-solid-state batteries - Yunting Wang; Gaohui Du; Di Han; Weihao Shi; Liming Wang; Libing Yao; Huayu Li; Jingyi Jing; Shaochen Wei; Shixian Chen; Wenqi Zhao; Qingmei Su (Chemical Engineering Journal, 2025)

Availability, mobility and reactivity of oxygen species in Ag/CeMnOx composite oxide for promoted catalytic soot combustion - Longwen Chen; Libing Guo; Yingxi Wei; Guijing Xiao; Feng Liu; Yanwu Chen; Xiaojing Jin; Yongyang Zhu; Haowei Huang; Yifan Lin (Journal of Environmental Chemical Engineering, 2025)

Dual photoelectric-photothermal effects synergistically overcome the cryogenic limits of aqueous supercapacitors - Chenyu Du; Chen Zhao; Zengying Zhao; Shuonan Wang; Yao Hao; Hua Gao; Libing Liao; Hao Liu (Chemical Engineering Journal, 2025)

A Dirac δ function based frequency-domain algorithm for the offshore structural vibration considering non-zero initial conditions - Dongan Li; Shengli Chen; Libing Zou; Xiang Yuan Zheng (Ocean Engineering, 2025)

Boosting interfacial charge transfer for efficient photothermal oxidation of benzyl alcohol to benzaldehyde by tin-doped titanium dioxide - Houkui Xiang; Junjie Cheng; Luo Tao; Sheng Yang; Guoliang Zhang; Jingxian Chen; Yingying Wang; Songbo Zhou; Haifeng Yu; Libing Qian; Tongqiang Xiong (Chemical Engineering Journal, 2025)

Dry-processing of VN quantum dots/N, O, S-doped hierarchical porous carbon electrodes with high sulfur-loading for practical lithium-sulfur batteries - Shixian Chen; Gaohui Du; Yan Cheng; Di Han; Jiahao Deng; Yunting Wang; Huayu Li; Libing Yao; Dong Wang; Qingmei Su; Bingshe Xu (Chemical Engineering Journal, 2025)

Pilot work of the 10K Chinese People Genomic Diversity Project along the Silk Road suggests a complex east-west admixture landscape and biological adaptations - Guanglin He; Hongbing Yao; Shuhan Duan; Lintao Luo; Qiuxia Sun; Renkuan Tang; Jing Chen; Zhiyong Wang; Yuntao Sun; Xiangping Li; Liping Hu; Libing Yun; et al. (Science China Life Sciences, 2025)

Clinical relevance of lung microbiota composition in critically ill children with acute lower respiratory tract infections: insights from a retrospective analysis of metagenomic sequencing - Zhiyu Men; Zhiheng Chen; Xinmeng Gu; Yichen Wang; Xingheng Zhang; Fang Fang; Meili Shen; Saihu Huang; Shuiyan Wu; Libing Zhou; Zhenjiang Bai (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Multicolor luminescence of carbon Dots: From mechanisms to applications - Man Jiang; Yuzhu Sun; Mingyue Chen; Hongfei Ji; Ying Liu; Ruijie Qin; Xiyan Li; Hongling Gao; Ruizhong Zhang; Libing Zhang (Chemical Engineering Journal, 2024)

High adsorption of Cu(II) in novel thiacalix[4]arene/acrylic polymer/diatomite fast fabricated by electron beam irradiation: Controllable microstructures, adsorption performance and mechanism - Xiuqin Tang; Guowen Hu; Zhiyuan Chen; Libing Qian; Chunqing He; Tao Chen; Jie Gao; Yuan Zhao; Xiaobing Han (Chemical Engineering Journal, 2024)

Ultrasensitive triethylamine gas sensors with ZnSe nanospheres/nest-like Cr-doped MoO3 - Xiangyun Tan; Li Wang; Xi Chen; Haoliang Zhang; Jiacheng Guo; Zhihu Dong; Libing Qian; Zhiyuan Chen; Chunqing He (Journal of Hazardous Materials, 2024)

Simultaneous modification of emission spectrum and trap distribution for achieving self-trapped excitons-based white afterglow - Huanxin Yang; Xiangxiang Chen; Haolin Lu; Wenda Sun; Yue Li; Yuhai Zhang; Yanjie Liang; Guankui Long; Libing Zhang; Xiyan Li (Chemical Engineering Journal, 2024)

Structure elucidation and antiviral activity of a cold water-extracted mannogalactofucan Ts1-1A from Trametes sanguinea against human cytomegalovirus in vitro - Yiran Wang; Mengxia Yan; Panpan Zhang; Xinna Wu; Siyang Huang; Siru Chen; Yizhou Rong; Yunjie Sheng; Yangyang Wang; Genxiang Mao; Libing Chen; Sanying Wang; et al. (Carbohydrate Polymers, 2024)

Rapid authentication of characteristic milk powders by recombinase polymerase amplification assays - Cang Zhou; Libing Liu; Jia Chen; Qi Fu; Zhimin Chen; Jinfeng Wang; Xiaoxia Sun; Lianfeng Ai; Xiangdong Xu; Jianchang Wang (Food Chemistry, 2024)

A lightweight bladder tumor segmentation method based on attention mechanism - Xiushun Zhao; Libing Lai; Yunjiao Li; Xiaochen Zhou; Xiaofeng Cheng; Yujun Chen; Haohui Huang; Jing Guo; Gongxian Wang (Medical & Biological Engineering & Computing, 2024)

Depth effects on bacterial community altitudinal patterns and assembly processes in the warm-temperate montane forests of China - Libing He; Xiangyang Sun; Suyan Li; Wenzhi Zhou; Jiantao Yu; Guanyu Zhao; Zhe Chen; Xueting Bai; Jinshuo Zhang (Science of The Total Environment, 2024)

Near-infrared electrochemiluminescence of defect-rich molybdenum disulfide quantum dots for sensitive bioanalysis - Mingyue Chen; Yuzhu Sun; Hongfei Ji; Man Jiang; Wendong Liu; Mingzheng Shao; Zhe Hao; Hongyan Zhang; Xiyan Li; Yanfeng Dang; Ruizhong Zhang; Libing Zhang (Chemical Engineering Journal, 2023)

High-strength and recyclable hydroplastic films from hydrophobic cellulose nanofibers produced via deep eutectic solvents - Qianqian Chen; Meng Zhou; Jun Yuan; Jiaqian Cai; Hongxia Xie; Mengxiang Zhu; Libing Cai; Peng Wei; Chunyu Chang (Chemical Engineering Journal, 2023)

HucMSC-EVs Facilitate In Vitro Development of Maternally Aged Preantral Follicles and Oocytes - Ying-Yi Zhang; Weijie Yang; Yi Zhang; Zhanhong Hu; Yingyan Chen; Yerong Ma; Anran Yang; Zhan Shi; Hanjing Zhou; Peipei Ren; Libing Shi; Jiamin Jin; et al. (Stem Cell Reviews and Reports, 2023)
Follicle developmental capacity and oocyte quality decline with advanced maternal age. Extracellular vesicles from human umbilical cord mesenchymal stem cells (HucMSC-EVs) act as a potential therapeutic product in the treatment of age-related ovarian dysfunction. In vitro culture (IVC) of preantral follicles is a useful method for understanding the mechanism of follicle development and is a promising means for improving female fertility. However, whether HucMSC-EVs have beneficial effects on aged follicle development during IVC has not yet been reported. Our research demonstrated that follicular development with single-addition withdrawal of HucMSC-EVs was better than that with continuous treatment with HucMSC-EVs. HucMSC-EVs facilitated the survival and growth of follicles, promoted the proliferation of granulosa cells (GCs), and improved the steroid hormone secretion of GCs during IVC of aged follicles. Both GCs and oocytes could uptake HucMSC-EVs. Moreover, we observed elevated cellular transcription in GCs and oocytes after treatment with HucMSC-EVs. The RNA sequencing (RNA-seq) results further validated that the differentially expressed genes are related to the promotion of GC proliferation, cell communication, and oocyte spindle organization. Additionally, the aged oocytes displayed a higher maturation rate, presented less aberrant spindle morphology, and expressed a higher level of the antioxidant protein Sirtuin 1 (SIRT1) after treatment with HucMSC-EVs. Our findings suggested that HucMSC-EVs can improve the growth and quality of aged follicles and oocytes in vitro through the regulation of gene transcription, which provides evidence for HucMSC-EVs as potential therapeutic reagents to restore female fertility with advanced age. Graphical Abstract

The vertical distribution and control factor of microbial biomass and bacterial community at macroecological scales - Libing He; Xiangyang Sun; Suyan Li; Wenzhi Zhou; Zhe Chen; Xueting Bai (Science of The Total Environment, 2023)

The role of ectomycorrhization with Scleroderma sp. in promoting substrate nutrients mobilization under phosphorus-enriched compost amendment: A case study with Castanea henryi seedlings - Wangzun Chen; Libing He; Shiyi Tian; Deyi Yuan; Joseph Masabni; Huan Xiong; Feng Zou (Forest Ecology and Management, 2023)

Celsr3 Inactivation in the Brainstem Impairs Rubrospinal Tract Development and Mouse Behaviors in Motor Coordination and Mechanic-Induced Response - Boli Chen; Fuxiang Li; Bin Jia; Kwok-Fai So; Ji-An Wei; Yuchu Liu; Yibo Qu; Libing Zhou (Molecular Neurobiology, 2022)
Inactivation of Celsr3 in the forebrain results in defects of longitudinal axonal tracts such as the corticospinal tract. In this study, we inactivated Celsr3 in the brainstem using En1-Cre mice ( Celsr3 cKO) and analyzed axonal and behavioral phenotypes. Celsr3 cKO animals showed an 83% reduction of rubrospinal axons and 30% decrease of corticospinal axons in spinal segments, associated with increased branching of dopaminergic fibers in the ventral horn. Decreases of spinal motoneurons, neuromuscular junctions, and electromyographic signal amplitude of the biceps were also found in mutant animals. Mutant mice had impaired motor coordination and defective response to heavy mechanical stimulation, but no disability in walking and food pellet handling. Transsynaptic tracing demonstrated that rubrospinal axons synapse on spinal neurons in the deep layer of the dorsal horn, and mechanical stimulation of hindpaws induced strong calcium signal of red nuclei in control mice, which was less prominent in mutant mice. In conclusion, Celsr3 regulates development of spinal descending axons and the motor network in cell and non-cell autonomous manners, and the maturation of the rubrospinal system is required for motor coordination and response to mechanical stimulation.

Biallelic DNAH9 mutations are identified in Chinese patients with defective left–right patterning and cilia-related complex congenital heart disease - Weicheng Chen; Yuan Zhang; Libing Shen; Jialiang Zhu; Ke Cai; Zhouping Lu; Weijia Zeng; Jianyuan Zhao; Xiangyu Zhou (Human Genetics, 2022)

The miR-302s/367 Cluster Inhibits the Proliferation and Apoptosis in Sheep Fetal Fibroblasts via the Cell Cycle and PI3K-Akt Pathways - Xian Wu; Ruiying Tong; Xiuli Chen; Xinying Jiang; Xiaoying He; Libing Ma (Mammalian Genome, 2021)

The Responses of Maize Yield and Water Use to Growth Stage-Based Irrigation on the Loess Plateau in China - Ning Jin; Jianqiang He; Quanxiao Fang; Chao Chen; Qingfu Ren; Liang He; Ning Yao; Libing Song; Qiang Yu (International Journal of Plant Production, 2020)

Antibacterial and antiparasitic activities analysis of a hepcidin-like antimicrobial peptide from Larimichthys crocea - Libing Zheng; Yuan Li; Jun Wang; Ying Pan; Jia Chen; Weiqiang Zheng; Longshan Lin (Acta Oceanologica Sinica, 2020)

Evaluation of management procedures for a length-frequency data-limited fishery - Richard Kindong; Jiangfeng Zhu; Feng Wu; Libing Dai; Xiaojie Dai; Siquan Tian; Yong Chen; Meng Xia (Environmental Science and Pollution Research, 2019)

Detection of FOXO1 break-apart status by fluorescence in situ hybridization in atypical alveolar rhabdomyosarcoma - Libing Fu; Yaqiong Jin; Chao Jia; Jie Zhang; Jun Tai; Hongbin Li; Feng Chen; Jin Shi; Yongli Guo; Xin Ni; Lejian He (Science China Life Sciences, 2017)

Migration of photoinitiators from paper to fatty food simulants: experimental studies and model application - Bo Han; Li Ding; Rongxin Su; Lei Chen; Libing Wang; Wei Qi; Zhimin He (Food Additives & Contaminants: Part A, 2016)

Molecular cloning of vasa gene and the effects of LHRH-A on its expression in blue tilapia Oreochromis aureus - Jun Xiao; Yongju Luo; Libing Chen; Li Yang; Yulin Huang; Zhongbao Guo; Enyan Guo; Zhanyang Tang; Ming Zhang; Xi Gan (Fish Physiology and Biochemistry, 2013)